(untitled) (AYUSHDHARA, 2025)
Acharya Sushruta emphasises Siravedha (venesection) for localised diseases of the craniofacial, oral, nasal, ocular, and palatal regions as well as for disorders of the Manovaha Srotas like Apasmara and Unmad. Anatomical correlations can be used to validate its classical indications. Material and Methods: Conceptual study carried out by reviewing classical texts, contemporary science, journals, published research works. Results: At the Hanu Sandhi, venesection targets the facial, retromandibular, and pterygoid venous plexus, which communicate with intracranial sinuses, justifying its use in Apasmara. Sites such as Shankh-Keshant Sandhi, Apang, and Lalat involve branches of the superficial temporal, supraorbital, supratrochlear, and angular veins, explaining their role in cranial disorders. Urogata Siras near the chest influence Prana Vayu and Sadhaka Pitta via their proximity to the Hridaya region. Localized interventions include the Adhojihva Sira (deep lingual vein) in tongue and gum diseases, Talu Sira (palatal veins) in palatal disorders, Karnyorupari Siras (superficial temporal and posterior auricular veins) in ear pathologies, Phana Marma (lateral nasal vein) in nasal conditions, and Apang Marma (angular and infraorbital venous networks) in ocular and head diseases. Conclusion: These sites correspond to venous junctions with extensive extracranial–intracranial connections, enabling evacuation of vitiated Doshas, decongestion, and modulation of vascular and neural activity. Thus, Siravedha emerges as a rational therapeutic intervention for neurological and localized craniofacial disorders.